From Barriers to Breakthroughs: Rethinking Autonomous Vehicle Design for Visually Impaired Users - Myungbin Choi; Taehun Kim; Seungjae Kim; Taejin Kim; Wonjoon Kim (Applied Sciences)
The movement of visually impaired people is still limited, and they often require assistance from others. In this study, along with the development of autonomous driving technology, a future mobility design that will help visually impaired people conveniently move around was proposed. The Double-Diamond model, a representative UX evaluation method, was revised and used for the evaluation. After discovering the mobility problems of the visually impaired, we developed the problem into an idea and designed future mobility based on the idea. Then, it was delivered to visually impaired people, and a utility test was performed on the new concept and functions. Six functions were proposed in scenarios for each moving process, and the evaluation results showed that drop-off notification using multi-senses showed the highest utilization. It is hoped that the expansion of self-driving vehicles will increase the mobility of visually impaired people with difficulty driving.